Implementasi Akuntansi Sumber Daya Manusia Penyandang Difabel Daksa - Diska Arliena Hafni (Universitas Muhammadiyah Jakarta, 2020)
This study aims to find out the implementation of Human Resource Accounting in Difa City Tour and Transport-Yogyakarta. Human resources owned by Difa City Tour and Transport-Yogyakarta are persons with disabilities who work as motorcycle taxi drivers with a modified motorcycle fleet. Data collected through interviews and observations. Qualitative data are analyzed by describing, interpreting, and describing systematically collected data.Data analysis begins with data collection, data reduction, data presentation and drawing conclusions.The results showed that Difa City Tour and Transport-Yogyakarta treats its human resources as an asset.Difa City Tour and Transport-Yogyakarta creates a system of human resource management starting from recruitment, training and placement which is systematic, gradual and measurable.The evaluation method for human resources in Difa City Tour & Transport Yogyakarta in practice refers to the Human Resource Value Accounting method in the Non-monetary Model.